AUDIT-C as a possible source of referral during the COVID-19 pandemic for participants presenting patterns of high-risk alcohol consumption in a South African township - Lynne Goldschmidt; Buyisile Mncina; Malose Langa; Steven Rebello; Thokozile Budaza; Josephine Tshabalala; Yohannes Kinfu; Tom Achoki (BMC, 2023)
Abstract Background Unhealthy alcohol use is a leading contributor to premature death and disability worldwide. The World Health Organization's Global Status Report on Alcohol and Health ranked South Africa as having one of the riskiest patterns of alcohol consumption, which calls for intervention. Recognising the need for effective primary care interventions, particularly in the absence of appropriate alcohol-related harm reduction policies at national and local levels, this paper highlights the opportunities and challenges associated with a two-pronged, community-centred approach to the identification of unhealthy alcohol use and interventions. Methods This approach included the use of the Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) as a means of screening to identify individuals at moderate (score of 5-7) to high risk (score of 8 +) alcohol use, raising awareness, and investigating the potential utility of brief advice and referrals as a means of reducing risk. Results Of the 54,187 participants, 43.0% reported engaging in moderate-risk alcohol consumption, with 22.1% reporting high-risk alcohol consumption. Resistance to brief advice was observed to increase with higher AUDIT-C scores. Similarly, participants engaging in high-risk alcohol consumption were resistant to accepting treatment referrals, with fewer than 10% open to receiving a referral. Conclusions While men were most likely to report patterns of high-risk alcohol consumption, they were more resistant to accepting referrals. Additionally, participants who were willing to receive brief advice were often resistant to taking active steps to alter their alcohol use. This study highlights the need to consider how to prevent harmful patterns of alcohol use effectively and holistically, especially in low socioeconomic settings through primary health care and community services.